2017
DOI: 10.21276/aimdr.2017.3.2.an9
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Venous Pressure as a Predictor of Central Venous Pressure during Neurosurgical Procedures

Abstract: Background: Central venous pressure (CVP) measurement is a reliable method for evaluating intravascular volume status and cardiac function, but it is an invasive method that results in some well known complications. To compare CVP with peripheral venous pressure (PVP) transduced from a peripheral intra venous catheter and to assess the reliability of peripheral venous pressure (PVP) as a predictor of central venous pressure (CVP) in the setting of rapidly fluctuating hemodynamics during neurosurgical procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…In comparison, a last research reported by stated that the PVP and CVP were registered to the closest 1mm Hg at 5 minutes' interval [29]. These similarly conducted a study by [30].…”
Section: Venous Pressure Monitoringmentioning
confidence: 91%
“…In comparison, a last research reported by stated that the PVP and CVP were registered to the closest 1mm Hg at 5 minutes' interval [29]. These similarly conducted a study by [30].…”
Section: Venous Pressure Monitoringmentioning
confidence: 91%